The Phenomenon of “Indonesia Gelap” on Social Media: Sentiment Analysis and Public Opinion Polarization - Christiany Juditha (Jurnal Komunikasi, 2025)
This study aims to identify public sentiment and analyze opinion polarization related to the "Indonesia Gelap" phenomenon on social media. This phenomenon emerged as a form of public protest with government policies, which was expressed through the hashtag #IndonesiaGelap. The research method used Social Media Analysis (SMA). The results showed a significant spike in mentions, reach, and engagement on social media related to this phenomenon, especially in mid-February 2025 which was triggered by student demonstrations. Negative sentiment dominated the conversation, indicating public dissatisfaction with government policies. The polarization of public opinion was also clearly visible, with various groups having different views, especially regarding political figures and national issues. Social media has been shown to play a role as a trigger for polarization through the spread of emotional content and opinion manipulation. Meanwhile, news portals have the potential to form consensus through credible reporting. The study concludes that the  “Indonesia Gelap” phenomenon has sparked intense and polarized discussions on social media, with significant impacts on public opinion and social dynamics. The study recommends improving digital media literacy, developing responsible social media platforms, and strengthening regulations to address polarization.